The Evoked Potential Score for SSEP and BAEP—A Prognostic Marker for the Long-Term Neurological Outcome in Patients after Poor-Grade Subarachnoid Hemorrhage - Lisa I. Wadiura; Johannes Herta; Mario Mischkulnig; Dorian Hirschmann; Martin Borkovec; Arthur Hosmann; Andrea Reinprecht (Diagnostics, 2021)
Objective: Evoked potentials are widely used in comatose patients to evaluate neurological function; however, prognostic relevance in patients after SAH is barely investigated. Therefore, we aimed to investigate the prognostic value of the proposed Evoked Potential Score (EPS) for somatosensory (SSEP) and brainstem auditory evoked potentials (BAEP) on the neurological outcome in patients after poor-grade SAH. Methods: We retrospectively analyzed patients after poor grade SAH (Hunt and Hess (HH) grade IV and V) that were admitted to the ICU at the Department of Neurosurgery, MUV, between 2014 and 2017. Measurements of SSEP and BAEP were evaluated separately as well as in a combined model, using the EPS at admission and before ventilator weaning and correlated with the grade of the modified ranking scale at the last available follow up. Results: In total, 48 patients after SAH HH IV/V were included in this study. The EPS for SSEP at admission (p = 0.007) and both the EPS for SSEP (p = <0.0001) and BAEP (p = 0.036) before ventilator weaning were significant prognostic markers for neurological improvement at a mean follow-up period of 14.1 months. In addition, the combined model of the EPS for SSEP/BAEP performed as a prognostic marker for neurological improvement (“at admission” p = 0.007; “before ventilator weaning” p < 0.001). Conclusions: In the first series to date we found a high prognostic significance for the EPS as a combined model, as well as a separate analysis for SSEP and BAEP in patients after SAH IV and V. In the future, these findings potentially support physicians in ethically challenging decision-making processes and in advice for patients’ families under consideration of an individual evaluation of each patient.